الفلسطينيون: سبعونَ عاماً بين اللجوء و الشتات = The Palestinians: seventy years of refuge and displacement - Eid, Iyad Muhammad; Mohamad Diah, Nurazzura (University Malaya, 2018)
This study aims to examine the life of the Palestinian refugees which started in 1948 during the Israeli occupation in Palestine. This historical event, commonly known as the Nakba, transformed them from native citizens into refugees, struggling with instability and uncertainty in refugee camps. The study also presents how recent political conflicts in Iraq, Syria and the Gaza Strip have played a key role in forcing the Palestinian refugees to flee again to temporarily live in asylum countries such as Malaysia, taking it as a transitional destination until they are resettled in a third country. This study employed qualitative approach. To obtain relevant data, in-depth interviews were conducted with thirty Palestinian refugee families who currently stay in Malaysia under the mandate of the United Nations High Commissioner for Refugees (UNHCR) in Kuala Lumpur. All respondents were recruited using the purposive sampling technique. Data were transcribed and analyzed using the thematic approach. The findings of this study discovered the following: i) Palestinian refugees have lived in unsteady life from 1948 until today, ii) they have been moving from one transitional destination to another, spending seven decades as refugees particularly in Arab countries and iii) they make Malaysia as a transitional destination while waiting to move to another destination. In short, this article highlighted several issues of Palestinian refugees and their unstable lives as a result of multiple movements. This article too has included various viewpoints about displacement and proposed some recommendations so that many people will understand better the issues of refugee.